Post-translational Acetylation Control of Cardiac Energy Metabolism - Ketema, Ezra B.; Lopaschuk, Gary D. (Frontiers in Cardiovascular Medicine, 2021)
Perturbations in myocardial energy substrate metabolism are key contributors to the pathogenesis of heart disease. However, the underlying causes of these metabolic alterations remain poorly understood. Recently, post-translational acetylation-mediated modification of metabolic enzymes has emerged as one of the important regulatory mechanisms for these metabolic changes. Nevertheless, despite the growing reports of a large number of acetylated cardiac mitochondrial proteins involved in energy metabolism, the functional consequences of these acetylation changes and how they correlate to metabolic alterations and myocardial dysfunction are not clearly defined. This review summarizes the evidence for a role of cardiac mitochondrial protein acetylation in altering the function of major metabolic enzymes and myocardial energy metabolism in various cardiovascular disease conditions.